1998
DOI: 10.1007/s004170050121
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma of the eyelid: histological and immunohistochemical features with special respect to differential diagnosis

Abstract: Dot-like positivities for CK-20 or NF are important to prove MCC and to exclude SCCL in clinically and morphologically doubtful cases. Dot-like positivities for pan-CK favor MCC, but do not always exclude SCCL. NSE and CHR are of no value for the differential diagnosis of MCC and SCCL. Melanoma and lymphoma are ruled out by negativity for S100 and pan-CK, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
32
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 29 publications
3
32
0
5
Order By: Relevance
“…Our findings did not support those of others who have documented that 20% of lesions were located in the eyelid or perioral region. 28,29 We added one additional patient with MCC of unknown primary site to the few documented cases already in the literature. [30][31][32][33] MCC without a primary tumor location can be a diagnostic dilemma for the surgical pathologist because of its histologic similarities with poorly differentiated small cell and other neuroendocrine carcinomas.…”
mentioning
confidence: 99%
“…Our findings did not support those of others who have documented that 20% of lesions were located in the eyelid or perioral region. 28,29 We added one additional patient with MCC of unknown primary site to the few documented cases already in the literature. [30][31][32][33] MCC without a primary tumor location can be a diagnostic dilemma for the surgical pathologist because of its histologic similarities with poorly differentiated small cell and other neuroendocrine carcinomas.…”
mentioning
confidence: 99%
“…The growth pattern of that tumor resembles that of a Merkel cell tumor. Cytokeratin 20 was usually negative while thyroid transcription factor was positive in such small cell carcinomas, but there has been no equivalent report on animals [6,[9][10][11]. In our case, as necropsy was not performed, a metastatic neuroendocrine tumor including small cell carcinoma of lung, could not be completely excluded.…”
mentioning
confidence: 61%
“…It has been reported that an immunohistochemical examination using cytokeratin 20 is extremely useful in distinguishing Merkel cell tumors from trichoblastoma and sweat gland tumors [11]. Merkel cell tumors are characterized by perinuclear dot-like structures (keratin button) for cytokeratin 20 [10,11], but these pattern is not universally seen as is true of those in the present case [7].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Another epithelial marker which controls the determination and differentiation of cells is thyroid transcription factor 1 (TTF -1), consisting of epithelial cells of the thyroid gland, lung and One standard marker used in the diagnosis of neuroendocrine tumors is neuron-specific enolase (NSE) (ref. 22,23 ). More recently, markers used in the diagnosis of MCC are CD56 and NCAM (neural cell adhesion molecule) (ref.…”
mentioning
confidence: 99%